2009
DOI: 10.2165/00003088-200948050-00005
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolic Acid Exposure after Administration of Mycophenolate Mofetil in the Presence and Absence of Ciclosporin in Renal Transplant Recipients

Abstract: These findings are consistent with the hypothesis that cyclosporin inhibits the biliary secretion and/or hepatic extraction of MPAG, leading to a reduced rate of enterohepatic recirculation of MPA. Several concurrent mechanisms, such as cyclosporin-induced changes in renal tubular MPAG excretion and enhanced elimination of free MPA through competitive albumin binding with MPAG, can also contribute to the altered MPAG pharmacokinetics observed in the presence and absence of cyclosporin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…Cyclosporine has also been shown to significantly reduce MPA exposure due to inhibition of enterohepatic recirculation (34,35). Kuypers et al demonstrated that the AUC 0Y12 was 21% higher at 7 months and 45% higher at 12 months after cyclosporine withdrawal compared with patients who remained on standard doses of cyclosporine (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclosporine has also been shown to significantly reduce MPA exposure due to inhibition of enterohepatic recirculation (34,35). Kuypers et al demonstrated that the AUC 0Y12 was 21% higher at 7 months and 45% higher at 12 months after cyclosporine withdrawal compared with patients who remained on standard doses of cyclosporine (34).…”
Section: Discussionmentioning
confidence: 99%
“…Kuypers et al demonstrated that the AUC 0Y12 was 21% higher at 7 months and 45% higher at 12 months after cyclosporine withdrawal compared with patients who remained on standard doses of cyclosporine (34). Unlike cyclosporine, tacrolimus does not affect MPA absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic subanalyses of these trials confirmed that dose-corrected MPA exposure is lower in cyclosporine-treated patients compared with tacrolimus-and sirolimus-treated patients 196,219 and that the extent of this drug-drug interaction is cyclosporine dose/exposure dependent. 220 Of note, the differences in MPA exposure between the different study groups in the CNI minimization trials might have contributed to the clinical outcome as well. It is possible that in the Symphony study, the higher MPA exposure in the tacrolimus-treated group might have contributed to the lower incidence of acute rejection in this group compared with the low-dose and standard-dose cyclosporine group.…”
Section: Drug-drug Interactions With Concomitant Immunosuppressive Mementioning
confidence: 99%
“…46,219 Furthermore, in the CAESAR trial, the higher MPA exposure in the low-dose cyclosporine group might have compensated for the lower cyclosporine exposure in this group, resulting in similar acute rejection rates in the low-dose and the standard-dose cyclosporine group. 45,220 Finally, whether a patient is treated with cyclosporine or tacrolimus might have implications for the pharmacokinetics of the glucuronide metabolites of MPA as well. Dosenormalized AcMPAG exposure was reported to be higher in cyclosporine-versus tacrolimus-treated patients, 180,203,221 and as this MPA metabolite is pharmacologically active, this finding might be clinically relevant.…”
Section: Drug-drug Interactions With Concomitant Immunosuppressive Mementioning
confidence: 99%
“…No dosage adjustment in patient with renal impairment or haemodialysis is needed. In patients with a reduced glomerular filtration rate (GFR) a 3-to 6-fold higher MPAG area under the curve values were reported [55,56]. In combination with TAC a 50% lower dose of MMF compared to a combination with CsA is recommended as CsA inhibits the hepatic extraction of MPAG leading to a reduced rate of enterohepatic recirculation.…”
Section: Mycophenolic Acidmentioning
confidence: 99%